Захват магнитного потока и замороженное магнитосопротивление в Bi-ВТСП пленках - Суханов, А.А.; Омельченко, В.И. (Физика низких температур, 2001)
Проведены холловские и магниторезистивные исследования захваченных магнитных полей (ЗМП) в полученных магнетронным распылением Bi-ВТСП пленках. Показано, что ЗМП являются знакопеременными в плоскости пленки с характерным масштабом, меньшим 50 мкм. Изучены температурные зависимости замороженного магнитосопротивления (ЗМС) и ЗМП. Обнаружено, что при нагреве пленок захваченные магнитные поля и ЗМС уменьшаются до нуля при температуре, существенно меньшей температуры исчезновения магнитосопротивления, и для захвата после охлаждения в нулевом поле на зависимости величины ЗМП от температуры захвата наблюдается максимум. Проведено обсуждение и сопоставление экспериментальных данных с результатами расчетов в рамках модели сверхпроводящих контуров, что позволило определить вид и параметры функции распределения контуров по критическим полям и температурные зависимости критических полей. Hall-probe and magnetoresistance studies of trapped magnetic fields are carried out on Bi-containing high- Tc superconducting films obtained by magnetron sputtering. It is shown that the trapped magnetic fields are alternating in sign in the plane of the film on a characteristic scale of less than 50 μm. The temperature dependence of the frozen magnetoresistance and trapped magnetic fields is investigated. It is found that heating the films causes the trapped magnetic fields and frozen magnetoresistance to decrease to zero at a temperature substantially lower than the temperature at which the magnetoresistance vanishes, and for trapping after cooling in zero field a maximum appears on the curve of the trapped magnetic fields versus the trapping temperature. The experimental data are discussed and compared with the results of calculations in the model of superconducting loops, making it possible to determine the form and parameters of the distribution function of the loops over critical fields and the temperature dependence of the critical fields.